Home-School-Based Nutrition Intervention Program to Increase Fruit and Vegetable Consumption in Children and Adolescent: A Systematic Review - Nuraeni, Irma; Setiawati, Dina; Karimah, Ima; Miranti, Yuni (Jurnal Sehat Indonesia (JUSINDO), 2025)
Fruit and vegetable campaigns have been widely conducted in countries with school-based intervention programs as a promising strategy to improve eating habits, but no reviews have assessed the effectiveness of multicomponent home-school-based programs on daily fruit and vegetable intake. Through a systematic review of the literature, this study aims to determine the effectiveness of a home-school-based nutrition intervention program on children's and teenagers' consumption of fruits and vegetables. This research identified randomized controlled trials based in primary, middle, and high schools designed to increase daily fruit and vegetable intake. PubMed, Google Scholar, and Crossref were searched from 2013 to 2024. The six studies met all inclusion criteria. Three of the six studies’ findings indicate that home-school-based nutrition intervention programs significantly increase fruit and vegetable intake among children and adolescents. The amount of FV consumed by teenagers at follow-up was significantly correlated with the level of parental participation in the Boost intervention. Adolescents' consumption of fruits and vegetables increased significantly during the BALANCE program intervention. The three-year school-based multicomponent intervention group's children's daily intake of fruits and vegetables increased significantly. However 3 other literature studies did not increase fruit and vegetable consumption. This study references the best approaches and strategies to prevent non-communicable diseases. Multicomponent interventions with specific duration and sustainability in the future may have the potential to be effectively implemented.